(untitled) (Global Journal of Human-Social Science, 2024)
Introduction: Helicobacter pylori (H. pylori), a Gram-negative bacterium, poses a global health threat linked to chronic gastritis, gastric ulcers, and adenocarcinoma. This literature review addresses H. pylori challenges, emphasizing therapeutic resistance and modern treatment strategies.